2017
DOI: 10.1038/nrneurol.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Drugging the pain epigenome

Abstract: More than 20% of adults worldwide experience different types of chronic pain, which are frequently associated with several comorbidities and a decrease in quality of life. Several approved painkillers are available, but current analgesics are often hampered by insufficient efficacy and/or severe adverse effects. Consequently, novel strategies for safe, highly efficacious treatments are highly desirable, particularly for chronic pain. Epigenetic mechanisms such as DNA methylation, histone modifications and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 196 publications
1
44
0
Order By: Relevance
“…One way in which cell function can be impacted over long periods of time is through epigenetics ( Denk and McMahon, 2017 ). Indeed, the role of epigenetic mechanisms is increasingly being studied in the pain field ( Denk et al, 2016 ; Denk and McMahon, 2017 ; Niederberger et al, 2017 ), as well as in neuroscience in general ( Akbarian et al, 2015 ; Gray et al, 2015 ; Mo et al, 2015 ; Halder et al, 2016 ; Hannon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One way in which cell function can be impacted over long periods of time is through epigenetics ( Denk and McMahon, 2017 ). Indeed, the role of epigenetic mechanisms is increasingly being studied in the pain field ( Denk et al, 2016 ; Denk and McMahon, 2017 ; Niederberger et al, 2017 ), as well as in neuroscience in general ( Akbarian et al, 2015 ; Gray et al, 2015 ; Mo et al, 2015 ; Halder et al, 2016 ; Hannon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies showed amelioration of hyperalgesia or allodynia following pharmacological modulation of histone acetylation/deacetylation. 40,41 Fewer attempts have been made to therapeutically target DNA methylation – possibly due to the lack of drugs suitable for interfering with DNMTs function. Future studies may provide a deeper understanding of the activity and structure of the different DNMTs, enabling the development of specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…These epigenetic changes may contribute to the development of several pain symptoms and the manifestation of chronic pain. In addition to providing a valuable insight into the molecular mechanisms of pain development and chronic pain syndromes, some studies have provided evidence regarding the use of epigenetic modulation as a potential therapeutic option for cancer-related pain (91,93,94).…”
Section: Future Outlookmentioning
confidence: 99%